Application of Concept Maps and Critical Thinking Ability to Improve Writing Reports - Martono Martono; Susanti Susanti; Suprapti Suprapti (JETL (Journal of Education, Teaching and Learning), 2017)
This study was conducted in class VIII C SMP 21 Pontianak City in 2015/2016. The study focused on the material report. Materi subject matter for the report is required to master this material student. Students so that they can write a trip report or reports on the observed results. they report should refer to the nature report. The fact write in school, students have difficulty writing reports. efforts to improve the ability of students to write a report done by the application of concepts and critical thinking questions. The focus of this research is how the application of the concept maps and critical thinking in improving report writing capability class VIII C SMP 21 years of 2015/2016? The scope of the research is focused on a few sub focus namely research, planning, implementation, and the result. The research method is descriptive and qualitative research design form of class action. Results of research learning planning cycle 1 (APKG1) values obtained 85.00 (very good), 2 cycles values obtained 97.50 (very good). Learning implementation using APKG2, the activities of teachers in the first cycle, the first and second meetings have been categorized Very Good, with a value of 87.20. Activities teachers teach when the second cycle, the first meeting and the second is better, with a value of 88.80. If the student activity cycled see first, first and second meetings are very active and are included active. Good Cycle. This second, first and second meeting, there was an increase in the student activity is said to be better than the first. Every cycle and every member of the group to work independently and be careful in teaching. cycle values of individual students: the average is 79.39. There is a group formed in learning activities. The final average group value  84.00. Second cycle. Values of individual students from three aspects, the average is 79.39. value incomplete 26.8%. group value Rate Average 88.00. 87.56 absorptive capacity. There was an increase in the average value of cycle 1 to cycle 2, at 4. But the value of the individual is constant.